Developing Academic Leaders: Evaluation of a Leadership Development Intervention in Higher Education. (February 2021) - Zulfqar, Asia; Valcke, Martin; Quraishi, Uzma; Devos, Geert
Leadership development is not considered as a core component in higher education policies specifically when we examine the higher education polices of developing countries. To fill this gap, an intervention is designed to evaluate the impact of a leadership development program in academic leaders. The prime objective of this intervention was to promote awareness among university deans and heads by adopting transformational leadership in their leadership practices. An experimental research design was adopted to map the effects of a 6-week intervention and to evaluate the variations in related six transformational leadership behaviors. Up to 37 academic deans and heads from public universities were involved in this research. Content analysis was carried out to analyze the collected data. Bloom's taxonomy was adopted as a framework for the analysis. Three lower levels of Bloom's taxonomy were used to identify the awareness indicators. An extensive increase in awareness levels was identified in relation to all six transformational leadership behaviors, and more specifically, a prominent progress was observed at the application level. In addition to implications and limitations, directions for future research were also discussed.